DIFFICULTIES IN TEACHING FOREIGN LANGUAGES TO YOUNG LEARNERS - Shamsuddinova Ruqiyaxon; Jalolova M (TADQIQOTLAR, 2025)
Annotation: This article explores the key difficulties faced by teachers when teaching foreign languages to young learners. It examines challenges such as short attention spans, limited cognitive skills, mixed abilities, classroom management, lack of motivation, limited exposure outside the classroom, pronunciation and listening difficulties, and assessment issues. The article also offers practical suggestions for overcoming these challenges and highlights the importance of a supportive and engaging learning environment.